Adapting and Validating a Measurement Battery for Academic Cheating Proneness: Its Correlates among Nigerian In-School Adolescents - Gafar Isiaka (Asosiasi Asesmen Pendidikan (AAP), 2026)
Nigerian secondary school researchers face an urgent methodological crisis: no validated, culturally appropriate instruments exist for measuring academic cheating proneness and its key psychological correlates among adolescents in this context. This paper employs an instrument adaptation and psychometric validation design to address this gap, reporting the systematic cross-cultural adaptation of a four-instrument measurement battery comprising the Proneness to Academic Cheating Behaviours Questionnaire (PACBQ), the Self-Efficacy Questionnaire (SEQ), the Procrastination Scale (PS), and the Locus of Control Scale (LOCS). These four instruments were selected as a theoretically coherent package, collectively capturing the full psychological profile of the cheating-prone student within Social Cognitive Theory and Cognitive Behavioural Theory frameworks. Each instrument underwent expert panel appraisal, item deletion, cultural contextualisation, and linguistic simplification. Content validity was established through a five-member expert review panel, with inter-rater agreement exceeding 80%. Test-retest reliability, assessed on a pilot sample of 20 SS1 students at a two-week interval, yielded coefficients of 0.89 (PACBQ), 0.90 (SEQ), 0.90 (PS), and 0.92 (LOCS). The main study involved 102 students selected via multi-stage sampling. Implications for counselling practice and further psychometric development are discussed.